Mechanizmy obronne, katharsis i inne aspekty terapeutyczne przemiany psychiki bohatera powieści i filmu "Mechaniczna Pomarańcza" - Niemiec, Tomasz (Wydawnictwo "Smak Słowa", 2012)
There is a progressive change in recent years in the Polish bibliotherapy, that forces the need for a scientific journal, where works depicting the main currents of polish bibliotherapeutic thought can be published. Responding to these needs and expectations the biannual journal The Bibliotherapy Review has been published by the Institute of Psychology at University of Wrocław. First of all, there are published articles about topics included in the program of the Postgraduate Studies of Bibliotherapy at University of Wrocław. Editorial Board and the Editors are intended to guide the journal into the modern direction and way of thinking about bibliotherapy and work of bibliotherapists.
Keywords: biblioterapia; bibliotherapy; filmoterapia; bohater filmowy; bohater literacki; katharsis; Mechaniczna pomarańcza (film; 1971); Burgess, Anthony (1917-1993). - Mechaniczna pomarańcza; Kubrick, Stanley (1928-1999); psychoanaliza